Decision making in highway construction: a systematic review and future directions - Nur Afiqah, Mohd Radzi; Abdul Rahimi, Abdul Rahman; Doh, Shu Ing (Emerald Publishing Limited, 2021)
Purpose: Various approaches have emerged to assist practitioners in making more informed decisions in highway construction projects. However, industry practitioners are still using subjective ways to make decisions. Also, researchers have developed tools and techniques with similar objectives. Lack of information on what has been developed might lead to those issues. Therefore, this paper aims to review trends of evolution, pinpoint strengths and gaps in the literature and identifies potential future directions for decision-making research in highway construction projects.